PENGARUH LATIHAN BOX JUMP TERHADAP KEMAMPUAN SMASH BOLAVOLI PADA MAHASISWA PGSD FKIP UNIVERSITAS MUHAMMADIYAH TANGERANG - Natas, Ahmad Mukhlisin (UNIVERSITAS NEGERI MAKASSAR, 2018)
This study aims to determine the effect of box jump training on smash ability in volleyball games. By using the field experiment method. The population used was FKIP Muhammadiyah University Tangerang students with a sample of 20 PGSD FKIP Muhammadiyah University students taken by random sampling. The data analysis technique used was the t-test at a significant level of 95%. The results of the study show that; (1) There is a significant effect of box jump training on smash ability in volleyball games, proven t0 = 13,175> tt = 2,262, and (2) There is a significant difference in influence between box jump and control groups on the smash ability in volleyball games, proven t0 = 11,803> tt = 2,101